MANAJEMEN PROGRAM PENDIDIKAN KESETARAAN PAKET C (Lembaga Pengembangan Kinerja Dosen, 2022)
Well-managed education program management will be able to improve the quality of education even though it is through a gradual process . The purpose of this research was to find out how the package C equivalence management process at SKB Tasikmalaya City in improving the quality of education. This research was conducted because several problems were found that could affect the quality of education, including only a few students who mastered IT, the learning process was not controlled, the dissemination of information on ICT-based learning was not evenly distributed, students wanted easy and fast services, and the difficulty of students adapting with other participants. This research uses descriptive qualitative methods, which are problem solving obtained by describing the state of the object or research subject based on facts in the field. The data sources used are primary data and secondary data obtained from eight informants and institutional administrative data. Data collection techniques in this study are through observation, interviews, and documentation. The instruments used are observation and interview guidelines. Based on the results of the study, it was found that the management of the package C equivalence education program which includes aspects of planning, organizing, actuating, monitoring and evaluating functions, Overall, it has been in accordance with and is running in a structured manner and has achieved the expected goals. It can be concluded that the management of the package C equivalence education program at the Tasikmalaya City SKB can gradually improve the quality of education.